2021
DOI: 10.7759/cureus.13994
|View full text |Cite
|
Sign up to set email alerts
|

Cystic Nontubular Jejunal Duplication Cyst Presenting As Acute Intestinal Obstruction: A Surgical Challenge

Abstract: Enteric duplication cysts are rare congenital anomalies that present with a vague constellation of symptoms such as vomiting and abdominal distension. Of these, cystic nontubular jejunal duplication cysts comprise an exceedingly small subset. Here, we delineate the case of a two-month-old female baby who presented with symptoms suggestive of acute intestinal obstruction. Radiological workup divulged a cystic lesion, which was subsequently confirmed to be a cystic nontubular jejunal duplication cyst with extens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…7 In our case, a second operation decision was made as a result of fluoroscopy, and the diagnosis of the thoracic GID (jejunal) cyst was confirmed as a result of repeated operations. Syed et al 8 reported a rare jejunal duplication cyst with obstruction. Our case is a jejunal duplication cyst in the thorax that does not cause bowel obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…7 In our case, a second operation decision was made as a result of fluoroscopy, and the diagnosis of the thoracic GID (jejunal) cyst was confirmed as a result of repeated operations. Syed et al 8 reported a rare jejunal duplication cyst with obstruction. Our case is a jejunal duplication cyst in the thorax that does not cause bowel obstruction.…”
Section: Discussionmentioning
confidence: 99%